Intercultural Communicative Approach and English Language Learning in fourth grade students at Jesus Divino Maestro High School, Santa Cruz de Flores, Cañete, 2016. - Quispe Cuya, María del Carmen (2018)
The main purpose of this work is to support that Intercultural Communicative Approach is related to the English Language Learning in fourth grade students at Jesus Divino Maestro High School, Santa Cruz de Flores. This work is of quantitative approach, fundamental type, correlational design, the population and sample were the same, 23 students. The techniques used were a Likert scale questionnaire, approved by experts, and the binomial escalation. The students who learn English in the school appreciate the importance of culture in English Language Learning; their answers in the two instruments applied with them demonstrate it. It emphasizes the importance of the Intercultural Communicative approach through the four skills in English Language Learning. Recent research shows that Intercultural Communicative Approach should be applied in English Language Learning. After processing and analyzing the results and the hypothesis testing, the research concluded that methodology is significantly related to English Language Learning in fourth grade students at Jesus Divino Maestro School, Santa Cruz de Flores, Cañete in 2016, taking into account that the correlation degree between variables is positive and moderate, 0.562; furthermore, the level of significance is less than 0.05 with a 95% confidence interval.